A model based on meta-analysis to evaluate poor prognosis of patients with severe fever with thrombocytopenia syndrome - Liu, Zishuai; Jiang, Zhouling; Zhang, Ligang; Xue, Xiaoyu; Zhao, Chenxi; Xu, Yanli; Zhang, Wei; Lin, Ling; Chen, Zhihai (Frontiers in Microbiology, 2024)
Severe fever with thrombocytopenia syndrome (SFTS) patients is crucial to improving patient survival.Method: Retrieve literature related to fatal risk factors in SFTS patients in the database, extract the risk factors and corresponding RRs and 95% CIs, and merge them. Statistically significant factors were included in the model, and stratified and assigned a corresponding score. Finally, a validation cohort from Yantai Qishan Hospital in 2021 was used to verify its predictive ability.Result: A total of 24 articles were included in the meta-analysis. The model includes six risk factors: age, hemorrhagic manifestations, encephalopathy, Scr and BUN. The analysis of lasso regression and multivariate logistic regression shows that model score is an independent risk factor (OR=1.032, 95% CI 1.002-1.063, P = 0.034). The model had an area under the curve (AUC) of 0.779 (95%CI 0.669-0.889, P＜0.001).The validation cohort was divided into four risk groups with cut-off values. Compared with the low-medium risk group, the mortality rate of high-risk and very high-risk patients was more significant (RR =5.677, 95%CI 4.961-6.496, P＜0.001).The prediction model for the fatal outcome of SFTS patients has shown positive outcomes.